Simulation of performance enhancement of heat exchanger with twisted tapes using ANSYS software - Taufik Ramadhan Fitrianto; Suhanan (Badan Kerja Sama Teknik Mesin Indonesia, 2023)
Heat transfer effectiveness in a heat exchanger depends on the fluid flow through the exchanger. The heat transfer coefficient is directly proportional to the Nusselt number of the fluid flow. A higher Nusselt number indicates a greater heat transfer rate. The enhancement of heat transfer quality can be achieved by increasing the surface area for heat transfer, disrupting the boundary layer, and inducing swirl flow in the fluid. Twisted tape inserts are used in the heat exchanger to induce swirl flow. In this simulation, six types of inserts with a length of 2000 mm, width of 35 mm, and twist ratios of 2.5, 5.0, 7.5, 10, 12.5, and 15 were used. The mass flow rates of the fluid used were 0.4 kg/s, 0.6 kg/s, and 0.8 kg/s. The simulation was conducted using the ANSYS software with the Computational Fluid Dynamics (CFD) subprogram. The simulation results showed different flow patterns in each experiment. As the number of twists in the twisted tapes increased, the vortex flow in the fluid also increased. The highest performance was observed in the experiment using the twisted tape insert with 15 twists and a mass flow rate of 0.8 kg/s.